2020
DOI: 10.1101/2020.07.21.20151423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resveratrol and Copper for treatment of severe COVID-19: an observational study (RESCU 002)

Abstract: Background To be universally applicable in treatment of severe COVID-19, novel therapies, especially those with little toxicity and low cost, are urgently needed. We report here the use of one such therapeutic combination involving two commonly used nutraceuticals, namely resveratrol and copper in patients with this disease. This study was prompted by pre-clinical reports that sepsis-related cytokine storm and fatality in mice can be prevented by oral administration of small quantities of resveratrol and copp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Additionally, the co-incubation of cells with the SARS-CoV-2 and a concentration of 50 ĀµM of resveratrol for one hour showed to cause a reduction by 64% in virus infection, indicating a possible blockage of the virusā€™s ability to enter host cells [ 79 ]. In accordance with that, it has also been reported that the daily intake of 3 doses of 5.6 mg of resveratrol by COVID-19 patients showed a 50% reduction in the percentage of deaths in the treated group [ 80 ].…”
Section: Uptake Of Phenolic Compounds In Dietary Supplements In Covid-19supporting
confidence: 78%
“…Additionally, the co-incubation of cells with the SARS-CoV-2 and a concentration of 50 ĀµM of resveratrol for one hour showed to cause a reduction by 64% in virus infection, indicating a possible blockage of the virusā€™s ability to enter host cells [ 79 ]. In accordance with that, it has also been reported that the daily intake of 3 doses of 5.6 mg of resveratrol by COVID-19 patients showed a 50% reduction in the percentage of deaths in the treated group [ 80 ].…”
Section: Uptake Of Phenolic Compounds In Dietary Supplements In Covid-19supporting
confidence: 78%
“…In one study, a nearly two-fold reduction in mortality following treatment with resveratrol-copper was observed. In this study thirty patients with severe COVID-19 received, in addition to standard care, resveratrol ( 69 ) and copper at doses of 5.6 mg and 560 ng, respectively orally, once every 6 h, until discharge or death ( Mittra et al, 2020 ). Lianhua Qingwen prescription (capsules or granules) is an innovative patented Chinese medicine that is composed of 11 herbs with gypsum and menthol, and this preparation had antiviral activities against viral respiratory infections.…”
Section: Natural Products Against Respiratory Virusesmentioning
confidence: 99%
“…Even if they are attractive for their very limited toxicity, data are not sufficient to introduce further investigations in this literature review. [112][113][114]…”
Section: Dovepressmentioning
confidence: 99%